Habilidades blandas y capacidad emprendedora en los estudiantes de la Escuela Profesional de Administración de la Universidad Nacional de la Amazonía Peruana filial Requena 2025 - Garcia Chavez, Leonel (2025)
The final report aimed to identify the relationship between soft skills and entrepreneurial ability in students of the UNAP School of Business Administration, Requena 2025 branch. To this end, a descriptive-correlational approach with a non-experimental design was used. The sample consisted of 72 students, who were administered a questionnaire to collect the necessary data. The results of the analysis indicate that the majority of participants present an average level of soft skills development (32%). This is because they only occasionally establish clear rules when working in teams, and their ability to lead and coordinate group activities is intermittent. Furthermore, they have difficulty maintaining effective conversations with diverse people and rarely demonstrate a positive perception of themselves in different environments. On the other hand, the level of entrepreneurial ability is considered average (36%), since they only occasionally show motivation to overcome obstacles and establish clear objectives before starting projects. However, they have difficulty creating and maintaining networks of contacts, and they rarely manage to successfully implement original ideas in their initiatives. Finally, there is a high (Rho = 0.783) and statistically significant (p = 0.000) positive correlation between soft skills and entrepreneurial ability.